RESTful API Development for Student Schedule and Attendance Management in a Higher Education Environment - Rizky Parlika; Abidin Sulaiman; Riky Hermawan (Jurnal Serumpun Teknik Informatika, 2026)
This study presents the development of a RESTful API service to support student schedule and attendance management in a higher education environment. The research is motivated by the fact that schedule management and attendance recording are often still handled manually or by stand-alone applications, which complicates recap processes, attendance monitoring, and integration with existing academic information systems. The proposed system is implemented using the Laravel framework and MySQL database, where student, lecturer, course, schedule, and attendance entities are modeled in a structured way and exposed through RESTful endpoints over HTTP with JSON data format. The research adopts a software engineering approach consisting of requirement analysis, system design, implementation, and testing using Postman on a local development environment. The experimental results show that all CRUD operations and attendance recording functions work as expected, producing consistent JSON responses with appropriate HTTP status codes, indicating that the developed API is suitable to be used as a foundation for future integration with web and mobile applications